Syntactic Errors in Older Adults with Depression - Chengjie Xu; Nahathai Wongpakaran; Tinakon Wongpakaran; Teeranoot Siriwittayakorn; Danny Wedding; Pairada Varnado (Medicina, 2023)
Background and Objectives: This study investigated the differences in syntactic errors in older individuals with and without major depressive disorder and cognitive function disparities between groups. We also explored the correlation between syntax scores and depression severity. Materials and Methods: Forty-four participants, assessed for dementia with the Mini-Cog, completed the 15-item Geriatric Depression Scale (TGDS-15) and specific language tests. Following a single-anonymized procedure, clinical psychologists rated the tests and syntax scores. Results: The results showed that the depressive disorders group had lower syntax scores than the non-depressed group, primarily on specific subtests. Additionally, cognitive test scores were generally lower among the depressed group. A significant relationship between depression severity and syntax scores was observed (r = −0.426, 95% CI = −0.639, −0.143). Conclusions: In conclusion, major depressive disorder is associated with reduced syntactic abilities, particularly in specific tests. However, the relatively modest sample size limited the sensitivity of this association. This study also considered the potential influence of cultural factors. Unique linguistic characteristics in the study’s context were also addressed and considered as potential contributors to the observed findings.